Identification of drones in a defined territory - Nakonechnyy, A.; Berezhnyi, I. (Видавництво Львівської політехніки, 2018)
Different modern methods of detecting drones, which are based on various physical principles of signal transformation and processing, are examined and analyzed. The system of identification of drones is proposed, the basis of which is the analysis of signals of vibration and oscillations of the body. The work of the system is based on the processing of signals in time-frequency, wavelet area. After the identification of the drone is given a method of creating interference and interception, to further eliminate it.
Keywords: detection of quadcopter; neutralization of quadcopter; vibration of the body of the drone; identification of the drone; 65.011.56.001.12